A Statistical Study of the Spatial Extent of Relativistic Electron Precipitation With Polar Orbiting Environmental Satellites. Issue 11 (16th November 2017) - Shekhar, Sapna; Millan, Robyn; Smith, David
Abstract: Relativistic electron precipitation (REP) in the atmosphere can contribute significantly to electron loss from the outer radiation belts. In order to estimate the contribution to this loss, it is important to estimate the spatial extent of the precipitation region. We observed REP with the zenith pointing (0°) Medium Energy Proton Electron Detector (MEPED) on board Polar Orbiting Environmental Satellites (POES), for 15 years (2000–2014) and used both single‐satellite and multisatellite measurements to estimate an average extent of the region of precipitation in L shell and magnetic local time (MLT). In the duration of 15 years (2000–2014), 31, 035 REP events were found in this study. Events were found to split into two classes; one class of events coincided with proton precipitation in the P1 channel (30–80 keV), were located in the dusk and early morning sector, and were more localized in L shell (dL < 0.5), whereas the other class of events did not coincide with proton precipitation, were located mostly in the midnight sector, and were wider in L shell (dL ∼ 1–2.5). Both classes were highly localized in MLT (dMLT ≤ 3 h), occurring mostly during the declining phase of the solar cycle and geomagnetically active times. The events located in the midnight sector for both classes were found to be associated with tail magnetic field stretching which could be due to the fact that they tend to occur mostly during geomagnetically active times or could imply that precipitation is caused by current sheet scattering. Key Points: Based on L shell extent or dL, two distinct spatial scales of relativistic electron precipitation (REP) were found: dL < 0.5 and 1 < dL < 2.5 Using multiple POES satellites, MLT extent (dMLT) was determined to be <3 h for all events studied in 15 years (2000–2014) in all MLT sectors All the midnight events were associated with magnetic field tail stretching consistent with current sheet scattering